Derivational Affixes With The Special Reference To Silb's Comic Entitled Blood Bank - Marita Khoirunnisaa; Widyastuti Widyastuti (Humanitatis : Journal of Language and Literature, 2022)
This research aimed to identify the kinds of affixes, and to explain the forms also the meaning of each affixes in the translated korean comic entitled “Blood Bank.” This study used qualitative research which contain open class words and new words. The data are taken from korean comic that can be accessed through online webpage or website. Based on the research finding, the writer found that derivational affixes is the part of morphological analysis. A derivational affix is an affix which the one word is derived from another. The derived word is often originated from different word class or the original ones. Meanwhile, affix is a grammatical element that is combined with a word, phrase, or root to produce derived forms. Affix is oficially divided into three main types: prefix (occurs at the beginning or front of the word), suffix (occurs at the end or back of the word), and infixes (occurs in the middle or inside of the word.) The result of this research shows that derivational affixes are used in the comic entitled “Blood Bank” by Silb. There are only two types of affixes that are found in the comic.They are prefix dis-, re-, mis-, im-, in-, non-, un-, as-, and suffix –age, -al,-ance, -er, -ion, -ment, -ce, -ity, -ness, -ful, -ship, -ate, -en, -ize, -able, -ish, -less, -ly, -ous, -y. There were three types of affixes but the writer didn’t find any infixes in the comic. The functions of derivational affixes consist of noun forming, adjective forming, and verb forming.